Valorization of Waste for Welfare: A Synergy of Knowledge, Innovation, and Community Development - Widyaningsih, NiLuh (Indonesian Journal Publisher, 2025)
Waste management remains a classic issue in developing countries such as Indonesia. According to data from the National Waste Management Information System (SIPSN), the waste management performance in 2024 from 312 regencies/municipalities in Indonesia shows the following: waste reduction at 13.14%, waste handling at 46.73%, managed waste at 59.87%, and unmanaged waste at 40.13%. The shift in the waste management paradigm from the conventional collect-transport-dispose pattern to the implementation of the 3R concept (reduce, reuse, and recycle) highlights the need to build awareness of waste management at the upstream level, particularly in households and elementary schools. Waste has both utilitarian and economic value if managed properly. Waste valorization can enhance human resource capacity and household income. This activity is carried out through community service (PkM), which can involve academic institutions, the business sector, and the government through a Triple-Helix approach. Comprehensively, this activity is sustainable in supporting a circular economy. The PkM activity that has been implemented involves a waste bank that utilizes organic waste using Black Soldier Fly (BSF), as well as banks that have processed inorganic waste into other product forms. This PkM activity project is expected to develop a landscape of a community-based waste management system.